Clinical features of peri-implant medication-related osteonecrosis of the jaw: Is there an association to peri-implantitis?. Issue 12 (December 2016) - Troeltzsch, Matthias; Cagna, David; Stähler, Philip; Probst, Florian; Kaeppler, Gabriele; Troeltzsch, Markus; Ehrenfeld, Michael; Otto, Sven
Abstract: The purpose of this study was to examine the behavior of dental implants in patients diagnosed with MRONJ and to analyze the characteristics of peri-implant MRONJ. It was hypothesized that peri-implant parameters are not associated with peri-implant MRONJ. A retrospective study design was selected to address the research purpose. Patients with confirmed MRONJ and the simultaneous presence of dental implants who presented between 2010 and 2016 served as the study cohort. Predefined inclusion and exclusion criteria were applied. Demographic, clinical and radiological data were collected and analyzed statistically with respect to the variable scale (significance level p ≤ 0.05). The study sample was composed of 34 patients (female: 16; male: 18; average age: 70.6 years) with a total of 117 dental implants the majority of whom had received antiresorptive drug therapy within oncologic treatment protocols. Peri-implant MRONJ occurred in 15 patients (44%). Signs of peri-implantitis (present around 46/117 implants; 39%) appeared to be associated with the occurrence of peri-implant MRONJ. Patients receiving antiresorptive drugs in high doses seem to be at risk of developing MRONJ in the vicinity of dental implants. Peri-implantitis may be associated with the etiology of peri-implant MRONJ.